Comparison of VIKOR and TOPSIS Methods in Multiresponse Taguchi Optimization - Suniantara, I Ketut Putu; Putra, I Gede Eka Wiantara (LPPM Undiksha, 2018)
Multirepon optimization in the Taguchi method can be done by using the VIKOR and TOPSIS approach, which are based on the concept that the best chosen alternative not only has the shortest distance from a positive ideal solution, but also has the longest distance from the negative ideal solution. The basic concept of these two methods is to determine the ranking of existing samples by looking at the results of the utility (S), regrets (R) and solution distances as the best alternatives for each sample. This study aims to obtain significant process variables on the brightness and soreness response variables in the envelope making process by using VIKOR and TOPSIS method approaches, and comparing the results of VIKOR and TOPSIS optimization. The results showed that the two methods produced process optimization in setting variables that were not the same. The VIKOR method produced a setting variable namely A3B2C1D1 while the TOPSIS method produced a setting variable A1B1C3D3. Looking at the value of the two methods, the VIKOR method produced a better estimated value of the brightness parameters and TOPSIS produced a better estimate value for the silence parameter.